The Value of Routine Polymerase Chain Reaction Analysis of Intraocular Fluid Specimens in the Diagnosis of Infectious Posterior Uveitis. (22nd October 2013) - Scheepers, Marius A.; Lecuona, Karin A.; Rogers, Graeme; Bunce, Catey; Corcoran, Craig; Michaelides, Michel
Abstract : Objective . To assess the value of routine polymerase chain reaction (PCR) analysis on intraocular fluid from patients presenting with a first episode of suspected active infectious posterior uveitis in a population with a high prevalence of human immunodeficiency virus infection. Design . Retrospective, interventional case series. Participants . 159 consecutive patients presenting at a tertiary care hospital over a five-year period. Methods . PCR analysis was performed for cytomegalovirus, varicella zoster virus, herpes simplex virus types 1 and 2, Toxoplasma gondii, and Mycobacterium tuberculosis . Results . PCR analysis confirmed the initial clinical diagnosis in 55 patients (35%) and altered the initial clinical diagnosis in 36 patients (23%). The clinical diagnosis prior to PCR testing was nonspecific (uncertain) in 51 patients (32%), with PCR providing a definitive final diagnosis in 20 of these patients (39%); necrotizing herpetic retinopathy and ocular toxoplasmosis were particularly difficult to diagnose correctly without the use of PCR analysis. Conclusion . The clinical phenotype alone was unreliable in diagnosing the underlying infectious cause in a quarter of patients in this study. Since the outcome of incorrectly treated infective uveitis can be blinding, PCR analysis of ocular fluids is recommended early in the disease even in resource poor settings.